Iowa RBA, August 6, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for August 6, 1996. Highlights of the update include a continued invasion of Red Crossbills with 17 additional reports from around the state as well as sightings of a Mississippi Kite and Little Blue Herons. Also included are handwritten notes for the next week's update with continued reports of Red Crossbills and numerous sightings of shorebirds, including Black-bellied Plovers, Stilt Sandpipers, and Ruddy Turnstones. Epson - sheet feed/flatbed